Macrozooplankton predation impact on anchovy (Engraulis encrasicolus) eggs mortality at the Bay of Biscay shelf break spawning centre. (23rd November 2014) - Albaina, Aitor; Irigoien, Xabier; Aldalur, Unai; Boyra, Guillermo; Santos, María; Estonba, Andone
Abstract: A real-time PCR based method involving a species-specific probe was applied to detect Engraulis encrasicolus eggs predation by the macrozooplankton community during the 2011 spawning season. Three locations along the shelf break presenting contrasting but high prey densities were sampled. A total of 840 individuals from 38 taxa of potential macrozooplankton predators were assayed for E. encrasicolus DNA presence and 27 presented at least one positive signal. Carnivorous copepods were responsible for the most predation events (66%) followed by euphausiids (16%), chaetognaths (5%), and myctophid fish (4%). Macrozooplankton predation on anchovy eggs followed a type-I functional response with daily mortalities <4% of available prey abundance suggesting a negligible impact on the species recruitment at the shelf break spawning centre.